Five new species of Anthocoptini from China (Acari: Eriophyidae) - Xue, Xiao-Feng; Song, Zi-Wei; Hong, Xiao-Yue (Zootaxa, 2010)
Five new species in the tribe Anthocoptini of the Eriophyidae (Acari: Eriophyoidea) from China are described and illustrated. They are Vittacus shaoguanicus sp. nov. on Carmona retusa (Vahl) Masam. (Boraginaceae), Vittacus cornusis sp. nov. on Cornus officinalis Sieb. et Zucc. (Cornaceae), Aculops buddlejaes sp. nov. on Buddleja lindleyana Fort. (Buddlejaceae ), Aculodes tsukushiensis sp. nov. on Elymus tsukushiensis Honda var. transiens (Hack.) Osad (Poaceae) and Tegolophus spathaceae sp. nov. on Fargesia spathacea Franch. (Poaceae, Bambuseae). All the new species described herein are vagrants on the respective host plant.